Analisis Kejadian Infeksi Saluran PernafasanAkut pada Balita di Puskesmas Talang Padang Kabupaten Empat Lawang - Murti; Harokan, Ali; Zaman, Chairil (Avicenna: Jurnal Ilmiah, 2025)
Background: The incidence of ARI in toddlers is ranked as one of the 10 most common diseases at the Talang Padang Health Center. The prevalence of ARI in 2024 was 58.8% with the number of ARI sufferers in toddlers aged one to four years over the past 3 years increasing, namely in 2022 there were 47 toddlers, in 2023 there were 53 toddlers and in 2024 there were 64 toddlers. This study aims to determine the analysis of the incidence of acute respiratory infections in toddlers at the Talang Padang Health Center, Empat Lawang Regency in 2025. Methods: This study was conducted from May 22 to June 10, 2025. The design of this study used a cross-sectional approach. The study population was all visits by parents of toddlers who sought treatment at the Talang Padang Health Center in 2024, totaling 255 respondents, with a sample of 72 toddlers. The sampling method was random sampling by accidental sampling because respondents who happened to be found or were easy to reach and were efficient in time and cost. The inclusion criteria for this study were willingness to be respondents, cough, runny nose accompanied by fever for 14 days and residing in the Talang Padang Health Center work area, while the exclusion criteria were respondents who moved residence. Data collection and retrieval using a questionnaire. Data analysis using the chi-square test and multiple logistic regression. Results: The results of statistical test analysis using Chi-Square statistical test and logistic regression where the results showed a significant relationship (pValue <0.05) for the variables of education (pValue = 0.00), knowledge (pValue = 0.00), breastfeeding (pValue = 0.00), immunization status (pValue = 0.00), smoking habits (pValue = 0.01), use of mosquito repellent (pValue = 0.01), housing density (pValue = 0.00), ventilation (pValue = 0.00) and use of cooking utensils (pValue = 0.00), and there was no relationship between gender (pValue = 0.85) and the incidence of ARI. From the results of the multivariate statistical test, it was obtained that the dominant factor in the occurrence of ARI was the use of cooking utensils (pValue = 0.02; OR = 79.97), meaning that the use of cooking utensils using firewood has a chance of causing ARI in toddlers as much as 79.97 times compared to the use of cooking utensils without firewood. Conclusion: It is expected to improve the performance program for handling ISPA in toddlers in the working area of ​​the Talang Padang Health Center such as increasing community education, strengthening early detection, and opening house ventilation for good air circulation Keywords: Cooking Utensils, Toddlers, ISPA, Health Center